2019
DOI: 10.1155/2019/5158308
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes, Atrial Fibrillation, and Direct Oral Anticoagulation

Abstract: Type 2 diabetes (T2D) is an independent risk factor of stroke and systemic embolism in patients with atrial fibrillation (AF), and T2D patients with AF-associated stroke seem to have worse clinical outcome and higher risk of unfavorable clinical course compared to individuals without this metabolic disorder. Long-term anticoagulation is indicated in majority of T2D patients with AF to prevent adverse AF-associated embolic events. Direct oral anticoagulants (DOACs), direct oral thrombin inhibitor dabigatran, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…Furthermore, warfarin inhibits the vitamin K-dependent gamma-glutamyl carboxylation of proteins, including matrix Gla protein and osteocalcin (bone Gla protein); therefore, the use of warfarin may increase the risk of vascular calcification and osteoporotic bone fracture in diabetic AF patients [38]. Our study supported the advantages of DOACs over warfarin regarding efficacy and safety in AF patients across a broad spectrum of HbA1c levels [34,38,39]. However, further randomized and prospective studies assessing the safety of DOACs vs. warfarin in patients with concomitant AF and type 2 DM are warranted.…”
Section: Comparisons Of Doacs and Warfarin In Different Hba1c Categoriessupporting
confidence: 66%
“…Furthermore, warfarin inhibits the vitamin K-dependent gamma-glutamyl carboxylation of proteins, including matrix Gla protein and osteocalcin (bone Gla protein); therefore, the use of warfarin may increase the risk of vascular calcification and osteoporotic bone fracture in diabetic AF patients [38]. Our study supported the advantages of DOACs over warfarin regarding efficacy and safety in AF patients across a broad spectrum of HbA1c levels [34,38,39]. However, further randomized and prospective studies assessing the safety of DOACs vs. warfarin in patients with concomitant AF and type 2 DM are warranted.…”
Section: Comparisons Of Doacs and Warfarin In Different Hba1c Categoriessupporting
confidence: 66%
“…Although some subanalyses of phase III clinical studies, 95 registries, and small‐sample prospective trials 96 have reported comparable efficacy and safety of NOACs in patients with or without DM, the original studies were not explicitly designed to examine the effect of DM on clinical outcomes in AF patients treated with NOACs versus warfarin. The impact of DM management on AF anticoagulation outcomes and drug interactions between NOACs and common antidiabetic agents remain areas in need of further study 97 …”
Section: Effect Of Lrfm On Af Management Strategiesmentioning
confidence: 99%
“…The impact of DM management on AF anticoagulation outcomes and drug interactions between NOACs and common antidiabetic agents remain areas in need of further study. 97 The effect of high BP on anticoagulation-associated intracranial hemorrhage or hemorrhagic expansion is variably reported. [98][99][100] For AF patients, higher BP has been associated with an increased risk of thromboembolic complications.…”
Section: Anticoagulationmentioning
confidence: 99%
“…Diabetes health management strategy based on internet plus graded diagnosis and treatment strategy risks to patients (3). Previous studies have shown that the continuous and stable control of blood glucose (4), blood pressure (5) and blood lipids (6) can significantly reduce the occurrence and development of acute and chronic diabetes complications. The most recent American Diabetes Association (ADA) guidelines suggest that glycosylated hemoglobin (HbA1c) should be controlled below 7.0%, and blood pressure should be controlled below 140/ 90 mmHg (blood pressure of patients with cardiovascular risk factors should be controlled below 130/90 mmHg) (7).…”
Section: Original Articlementioning
confidence: 99%